Knowledge, attittudes and practices of healthcare workers about prevention and control of multidrug-resistant tuberculosis at Botsabelo Hospital Maseru, Lesotho - Adebanjo, Omotayo David (University of Limpopo ( Medunsa Campus), 2011)
Background: Tuberculosis is one of the major public health problems in Lesotho. With the occurrence of multi-drug resistant tuberculosis, little is known about the views of health care workers on this disease. The aim of this study was to investigate the knowledge, attitudes, and practices of healthcare professionals about prevention and control of MDR-TB at Botsabelo hospital, situated in Maseru, Lesotho. Methods: This study was conducted by means of a semi-structured, anonymous, and self-administered questionnaire that was sent to health care workers. Returned questionnaires were collected through designated boxes stationed at selected places at the study site from 23rd September to 13th October 2010. The investigator and his assistants collected the returned questionnaires on the 15th October 2010. Results: The results of this study indicate that, overall, less than half (47.3%) of respondents had good level of knowledge about MDR-TB; but the overwhelming majority of them held negative attitude towards patients with MDR-TB. Further analysis showed that the level of knowledge did not affect the attitude towards patients suffering from MDR-TB but it influenced their practices. Having good level of knowledge about MDR-TB was associated with good practices such as the use of protective masks and MDR-TB guidelines and involvement in educating patients about MDR-TB. Moreover, the findings of this study showed also that the attitude of respondents towards patients suffering from MDR-TB did not influence their practices. Conclusion: In conclusion, less than half of respondents had good level of knowledge about MDR-TB, but over 85.5% of them held negative attitude towards patients suffering from MDR-TB. Although the level of knowledge about MDR-TB was found not to have influenced the attitude of respondents towards patients suffering from MDR-TB; and that xi their attitude did not influence practices, good level of knowledge was positively associated with safer practices such as using protective masks, educating patients on MDR-TB, and referring to the MDR-TB guidelines manual. An educational remedial intervention is recommended.
Thesis (MPH)--University of Limpopo, 2011.
Keywords: Tuberculosis; MDR-TB